Impact of cerebral oxygen saturation on mortality and rehospitalisation in patients with heart failure and the role of physical activity as a modifying factor : the HARVEST-Malmö Study - Zaghi, Amir ; 0000-0001-9521-4068; Jujic, Amra ; 0000-0002-9506-0158; Zilic, Haris; Dieden, Anna ; 0000-0002-1041-937X; Bachus, Erasmus; Holm, Hannes; Magnusson, Martin ; 0000-0003-1710-5936 (Heart, 2025)
BACKGROUND: The cross-sectional association between cerebral tissue oxygen saturation (SctO 2) and heart failure (HF) has been previously studied, but the prognostic significance of SctO 2 in HF remains uncertain. This study aimed to assess the role of SctO 2 as a risk factor for all-cause mortality and rehospitalisation, as well as to explore the cross-sectional association between physical activity and SctO 2 in a Swedish HF cohort. METHODS: In 102 patients with HF (mean age 70.2 years (±12.4); 21.6% women), near-infrared spectroscopy was used to assess SctO 2. Adjusted Cox regression analyses were conducted to examine the associations between resting SctO 2 levels and all-cause mortality and the initial occurrence of postdischarge rehospitalisations. The associations between self-reported physical inactivity and SctO 2 were explored by using multivariable linear and logistic regression analyses. RESULTS: The median follow-up time to death of any cause and first-of-any rehospitalisation was 830 (IQR: 519-1283) and 208 (72-584) days, respectively. During follow-up, 31 (30.4%) patients died and 63 (61.8%) were rehospitalised. Higher SctO 2 was associated with lower risk of mortality (HR 0.86; 95% CI 0.77 to 0.95; p=0.002) but not with rehospitalisation risk (HR 0.96; 95% CI 0.90 to 1.02; p=0.162). Physical inactivity (≤1 hour per week of strenuous activity) was associated with lower SctO 2 (β-1.56; 95% CI -3.07 to -0.05, p=0.043). CONCLUSION: Higher SctO2 at rest is associated with lower risk of all-cause mortality but it was not possible to show significant association with first-of-any rehospitalisation risk in patients with HF. Physical inactivity is associated with lower cerebral oxygen saturation at rest. These findings could suggest SctO2 as a potential marker associated with long-term outcomes in HF, warranting larger confirmatory studies.
© Author(s) (or their employer(s)) 2025. Re-use permitted under CC BY. Published by BMJ Group.